2020
DOI: 10.4252/wjsc.v12.i10.1152
|View full text |Cite
|
Sign up to set email alerts
|

Pericyte-like differentiation of human adipose-derived mesenchymal stem cells: An in vitro study

Abstract: BACKGROUND Adipose-derived mesenchymal stem cells (ASCs) are characterized by long-term self-renewal and a high proliferation rate. Under adequate conditions, they may differentiate into cells belonging to mesodermal, endodermal or ectodermal lineages. Pericytes support endothelial cells and play an important role in stabilizing the vessel wall at the microcirculation level. The loss of pericytes, as occurs in diabetic retinopathy, results in a breakdown of the blood-retina barrier (BRB) and infil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 38 publications
(43 reference statements)
4
30
0
Order By: Relevance
“…The MSC nature of ASCs used in the present study was verified in previous works, where cells of the same stock were investigated [ 25 ]. In particular, they were immuno-positive for typical MSC markers (CD44, CD73, CD90 and CD105), and immunonegative for hematopoietic stem cell markers (CD14, CD34 and CD45).…”
Section: Methodssupporting
confidence: 67%
See 2 more Smart Citations
“…The MSC nature of ASCs used in the present study was verified in previous works, where cells of the same stock were investigated [ 25 ]. In particular, they were immuno-positive for typical MSC markers (CD44, CD73, CD90 and CD105), and immunonegative for hematopoietic stem cell markers (CD14, CD34 and CD45).…”
Section: Methodssupporting
confidence: 67%
“…Indeed, beneficial effects were reported in rodent models of DR following intravitreal injections of native or TGF-β1 pretreated ASCs [ 14 ]. Furthermore, in a previous investigation we were able to induce a pericyte-like differentiation by growing ASCs in a culture medium specifically designed for pericytes [ 25 ]. In our opinion, this strategy offers the advantage of obtaining pericyte-like ASCs still in the proliferative stage, more suitable to restore a functional BRB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Main results are summarized in Table 1 . A successful pericyte-like differentiation of ASCs was achieved by using specific culture media, as demonstrated by the expression of typical pericyte markers [α-smooth muscle actin, nerve/glial-antigen 2, platelet-derived growth factor receptor (PDGFR)] as well as by their perivascular localization in three-dimensional cultures[ 19 , 20 ]. In an in vitro model of the BRB, pericyte-like ASCs were also able to reinforce endothelial junctions, as indicated by the increased expression of VE-Cadherin, zone occludens-1 and occludin.…”
Section: Diabetic Retinopathymentioning
confidence: 99%
“…In an in vitro model of the BRB, pericyte-like ASCs were also able to reinforce endothelial junctions, as indicated by the increased expression of VE-Cadherin, zone occludens-1 and occludin. In these experiments, also trans-endothelial electrical resistance values were increased[ 20 ]. It is also suggested that a high glucose (HG) concentration does not affect the pericyte-like functions of ASCs[ 21 , 22 ].…”
Section: Diabetic Retinopathymentioning
confidence: 99%